Raden Saleh : The Beginning of Modern Indonesian painting / Werner Kraus ; Editor, Irina Vogelsang ; Penerjemah, Hendarto Setiadi. - KRAUS, WERNER; Irina Vogelsang; Hendarto Setiadi. (Goethe-Institut Indonesien, 2012)
369 hlm. : ilus. ; 36 cm